The Development of Human Resources Capacity on Children’s Forum in Tanjungpinang City Throught “Becoming Z Generation Researcher” Workshop: Pengembangan Kapasitas Sumber Daya Forum Anak Kota Tanjungpinang Melalui Workshop "Menjadi Peneliti Generasi Z" - Diah Siti Utari; Desmayati Arfa; Rianto Rianto; Raja Abumanshur Matridi (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
The big role which must be carried out by an organization called Tanjungpinang City Children's Forum requires the capacity of the organization's human resources to carry out both roles as pioneers, reporters, and participation in planning development to raise the issues of fulfilling children's rights. In addition, the characteristics of Children's Forum human resources are included in the generation Z group, which is known close to technology, which becomes the basis for this service activity. Through a collaboration, the Forum for Public Participation for the Welfare of Women and Children (PUSPA) Gurindam Tanjungpinang City which is also an independent partner of the Tanjungpinang city government also contributes by providing knowledge and skills in the use of application technology related to research methodologies required by the board of Tanjungpinang City Children's Forum through the Workshop of “Becoming Z Generation Researcher”. After this workshop, it is hoped that it will have an impact on increasing knowledge and skills which are useful in raising the development of phenomena and issues related to the fulfillment of children's rights in Tanjungpinang city. The location of this activity is centered in the hall of the Office of Women's Empowerment, Child Protection, and Community Empowerment (DP3APM) in Tanjungpinang City for a full day with the target group of representatives of the Village Children Forum administrators throughout Tanjungpinang city. Abstrak Besarnya peran yang harus dijalankan oleh organisasi Forum Anak Kota Tanjungpinang menuntut kapasitas sumber daya manusia organisasi dalam menjalankan peran baik sebagai pelopor, pelapor serta partisipasi dalam perencanaan pembangunan dalam mengangkat isu-isu pemenuhan hak anak. Karakteristik sumber daya manusia Forum Anak juga termasuk dalam kelompok generasi Z yang dikenal dekat dengan teknologi inilah sehingga menjadi dasar kegiatan pengabdian ini dilakukan. Melalui kolaborasi, Forum Partisipasi Publik untuk Kesejahteraan Perempuan dan Anak (PUSPA) Gurindam Kota Tanjungpinang sebagai mitra independen dari pemerintah daerah kota Tanjungpinang turut berkontribusi dengan memberikan pengetahuan dan keterampilan (skill) penggunaan teknologi aplikasi terkait metodologi penelitian yang diperlukan oleh pengurus Forum Anak Kota Tanjungpinang melalui Workshop “Menjadi Peneliti Generasi Z”. Kegiatan workshop ini diharapkan akan berdampak pada peningkatan pengetahuan dan keterampilan yang bermanfaat dalam mengangkat fenomena dan isu yang berkembang berkaitan dengan pemenuhan hak anak di Kota Tanjungpinang. Lokasi kegiatan dipusatkan di Aula Dinas Pemberdayaan Perempuan, Perlindungan Anak dan Pemberdayaan Masyarakat (DP3APM) Kota Tanjungpinang selama sehari penuh dengan kelompok sasaran perwakilan pengurus Forum Anak Kelurahan se-kota Tanjungpinang.